EFEITO DE TRICHODERMA SPP. SOBRE O CRESCIMENTO MICELIAL DE FUNGOS DO GÊNERO RIZHOCTONIA SOLANI - LIMA, Carlos Eduardo Braga Vieira,; NUNES, Tiago Calves,; CASANOVA, Evelin Arantes,; CELOTO, Mercia Ikarugi Bomfim, (ANAIS DO ENIC, 2025)
-